(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to find out the evaluation of the service system at the One Stop Integrated Investment and Services in Pangkep Regency. This study used descriptive qualitative research methods. The informants in the study were 12 people. The data collection technique used interviews, observation, and documentation. The results showed that the effectiveness application of online-based service systems was quite effective from the aspect of achievement objectives and forms of implementation based on IKM each 6 months. But constrained on servers, networks, and community operations. Service system efficiency online-based was efficient in terms of cost and time. Responsiveness application of online-based service systems was good in terms of response and community satisfaction. The accuracy in application was correct from the aspect accuracy of purpose, while the aspect of accuracy of benefits, had not been maximized because some people had not been able to access services online.Keywords: Evaluation, Public Service, and One Stop Integrated Service.This study aimed to find out the evaluation of the service system at the One Stop Integrated Investment and Services in Pangkep Regency. This study used descriptive qualitative research methods. The informants in the study were 12 people. The data collection technique used interviews, observation, and documentation. The results showed that the effectiveness application of online-based service systems was quite effective from the aspect of achievement objectives and forms of implementation based on IKM each 6 months. But constrained on servers, networks, and community operations. Service system efficiency online-based was efficient in terms of cost and time. Responsiveness application of online-based service systems was good in terms of response and community satisfaction. The accuracy in application was correct from the aspect accuracy of purpose, while the aspect of accuracy of benefits, had not been maximized because some people had not been able to access services online.Keywords: Evaluation, Public Service, and One Stop Integrated Service.